Influencia de las relaciones interpersonales en el clima laboral de los colaboradores en la empresa de transportes Rodrigo Carranza SAC - Trujillo: 2016. - León Cruz, Mónica Judith (2017)
This research has had as a fundamental purpose explain the influence of interpersonal relations in the work environment of the co-workers in the transport undertaking Rodrigo Carranza SAC - Trujillo: 2016. The study is descriptive, non-experimental design, cross-sectional-correlational study. It is made with a non-probabilistic sample of 231 collaborators, with whom they work by applying the methods and techniques of quantitative and qualitative investigation. From the results it can be deduced that in this company there is a deficient labor climate, by inadequate interpersonal relations, low level of internal communication, high individualism index, low level of poor leadership and team work. Therefore having the information required to address the challenges the company faces, you must work on the improvement of the working environment of the organization which will have an impact on the increase of the motivation of workers, will help to improve the production, efficiency, results and good treatment toward colleagues and clients.